Oral potentially malignant disorders-What the dentist should know - Iparraguirre Nuñovero, Marcos Felipe (2020)
Objective: The objective of this study is to update scientiﬁc knowledge about OPMDs, emphasizing epidemiological data, clinical appearance, symptomatology, diﬀerential diagnosis and therapeutic management, as well as highlighting the role of the general dentist in the clinical examination. Material and methods: A literature search was carried out, making use of the keywords “Leukoplakia”, “Erythroplasia”, “Cheilitis”, “Nevus, Pigmented”, “Oral Submucous Fibrosis” and “Lichen Planus”. Prioritizing articles published in the last 5 years on the scientiﬁc databases “Medline”, “Pubmed” and “SciELO”. Results: As a result of the search, 165 articles were obtained, which were carefully reviewed to preserve only those that were dedicated to describe, compare or treat lesions with malignant potential, including relevant data such as epidemiology, clinical appearance, symptomatology, diﬀerential diagnosis and management. therapeutic. In this way, the study was limited to 41 articles. Conclusions: By taking preventive measures, as well as through a clinical examination of soft tissues, early detection of potentially malignant disorders can be facilitated. The removal of suspicious lesions or a control of their carcinogenic conditions can largely prevent the development of malignant tumors.